Rotulamentos de constelações de sinais uniformes e dadeias de particionamentos Ungerboeck hiperbólicas sobre o bitoro - Eduardo Michel Vieira Gomes (2017)
In this work, labels for geometrically uniform codes on the double torus are constructed from the using of Tiling groups. From this approach, it was possible to obtain at least one labeling group for each one of the 11 regular tesselations existing on the double torus using Fuchsian triangular groups. In addition, extensions of these labeling groups are obtained, in order to generate new codes. Moreover, partitioning chains for geometrically uniform codes are constructed by groups of soluble labels and, in some cases, it is obtained hyperbolic Ungerboeck partitions for the surface